Facebook Use and Public Participation in Science: A Comparison Between the General Public and Users of a Science Facebook Fan Page - Cheng-Ying Wu; Tsung-Jen Shih (International Telecommunications Society (ITS), 2017)
Investigating the role of SNSs in engaging the public in scientific affairs is necessary in the modern society where risk and scientific innovations bear a high level of uncertainty. This study employs the O-S-O-R model in its attempt to examine the impact of SNSs on civic activism and the potential mediating role of self-efficacy and scientific knowledge. It is noteworthy that this study utilizes data collected from two different populations –the general public and the users of the Facebook fan page “Pansci.com,” the biggest scientific online group in Taiwan. Based on a total sample size of 1,960, we found that Facebook use increases knowledge only for “Pansci.com” users. Moreover, Facebook use is positively related to self-efficacy and public participation in both samples. However, its effect on self-efficacy is stronger for “Pansci.com” users. Quite differently, the effect of self-efficacy on participation is stronger for the general public. Lastly, self-efficacy, but not knowledge, serves as a significant mediator between Facebook use and public participation in both samples. Implications of these findings will be discussed.
Keywords: 330; Social Network Sites; Facebook; Efficacy; Science Communication; Public Participation